THE RELATIONSHIP OF FORGIVENESS AND RELIGIUSITY WITH THE HAPPINESS OF CLASS XI STUDENTS IN SMASTATE 1 BUILDING ANCIENT - Fahrizalsyah Harahap; Hasanuddin Hasanuddin; M. Abrar Parinduri (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
Empirically, this study aims to see the relationship between forgiveness and religiosity with happiness in class XI students at SMAN 1 Bangun Purba. The population in this study was 190 students and the sample was 123 students where the sample was taken using proportionate stratified random sampling. Data collection techniques are questionnaires and documentation, data analysis is done by product moment correlation, hypothesis testing t test, F test, and determination test. The results showed that: (1) There was a significant positive relationship between forgiveness and religiosity with happiness as seen from the significance value of 0.001 < 0.005. The contribution of forgiveness and religiosity is seen from the value of the coefficient of determination (R2) = 0.682 or 68.2%. (2) There is a significant positive relationship between forgiveness and happiness as seen from the significance value of 0.003 < 0.005. 3) There is a significant positive relationship between religiosity and happiness as seen from the significance value of 0.001 < 0.005. Thus, it can be concluded that there is a significant relationship between forgiveness and religiosity with happiness in class XI students at SMKN 1 Bangun Purba.